Effect of uncoated and coated diamond on the compressive properties of porous aluminium composites - Parveez, Bisma; Jamal, Nur Ayuni; Mohamed Saleem, Muhammad Raeez (Wiley, 2023)
Porous aluminium composites are structural and functional materials that have vast potential, due to their lightweight and high energy absorption capacity, especially in automotive and aerospace applications. In this study, the effect of varying content of uncoated and Titanium coated diamond particles on the compressive properties of porous aluminium composite was investigated. The composites were developed using powder metallurgy technique and porosity was attained by using polymethylmethacrylate (30 wt.%) as space holder material. The morphology of the pores was found to replicate the shape and size of polymethylmethacrylate particles, that were uniformly distributed in the composites. X-ray diffraction analysis confirmed formation of Aluminium carbide in uncoated diamond-based aluminium composites while negligible amount was present in titanium coated porous composites during sintering. The porosities of composites decreased with an increase in diamond content due to the incomplete decomposition of polymethylmethacrylate particles. Moreover, the maximum plateau stress and energy absorption capacity of 9.96 MPa and 1.7 Mj/m3 were obtained for the composites with 8 wt.% of titanium coated diamond particles. Thus, coating inhibits the formation of undesirable compounds and contributes to better interfacial bonding between matrix and reinforcement.